Bi-level energy management strategy for power-split plug-in hybrid electric vehicles: A reinforcement learning approach for prediction and control - Yang, Xueping; Jiang, Chaoyu; Zhou, Ming; Hu, Hengjie (Frontiers in Energy Research, 2023)
The implementation of an energy management strategy plays a key role in improving the fuel economy of plug-in hybrid electric vehicles (PHEVs). In this paper, a bi-level energy management strategy with a novel speed prediction method leveraged by reinforcement learning is proposed to construct the optimization scheme for the inner energy allocation of PHEVs. Firstly, the powertrain transmission model of the PHEV in a power-split type is analyzed detailedly to obtain the energy routing and their crucial characteristics. Secondly, Q-learning (QL) algorithm is applied to establish the speed predictor. Thirdly, the double QL algorithm is introduced to train an effective controller offline that realizes the optimal power distribution. Finally, given a reference battery state of charge (SOC), a model predictive control framework solved by the reinforcement learning agent with the novel speed predictor is proposed to build the bi-level energy management strategy. The simulation results show that the proposed method performs satisfying fuel economy in different driving scenarios while tracking the corresponding SOC references. Moreover, the calculation performance also implies the potential online capability of the proposed method.